2016
DOI: 10.1097/md.0000000000004246
|View full text |Cite|
|
Sign up to set email alerts
|

Pneumothorax associated with nontuberculous mycobacteria

Abstract: The incidence of nontuberculous mycobacterial pulmonary disease (NTMPD) is increasing worldwide. Secondary spontaneous pneumothorax occurs as a complication of underlying lung disease and is associated with higher morbidity, mortality, and recurrence than primary spontaneous pneumothorax. We here investigated the clinical features and long-term outcomes of pneumothorax associated with NTMPD.We conducted a retrospective study on consecutive adult patients with pneumothorax associated with NTMPD at Fukujuji Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
3
21
0
1
Order By: Relevance
“…Our multivariate analysis also found that %FVC and BMI, which have been reported as important clinical factors in previous studies, were predictors of SGRQ scores [ 13 , 20 , 23 ], [ 34 , 35 ]. In a previous study, FVC showed a negative correlation with SGRQ scores [ 13 ], consistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our multivariate analysis also found that %FVC and BMI, which have been reported as important clinical factors in previous studies, were predictors of SGRQ scores [ 13 , 20 , 23 ], [ 34 , 35 ]. In a previous study, FVC showed a negative correlation with SGRQ scores [ 13 ], consistent with the findings in this study.…”
Section: Discussionsupporting
confidence: 82%
“…PFT was performed using an electronic spirometer (Chestac-9800 or HI-801; Chest M.I., Tokyo, Japan) when the patient was in a stable condition after study enrolment. MAC isolates were identified as previously described [ 20 ]. High-resolution computed tomography (HRCT) images were evaluated for cavitary lesions and the radiological pattern: nodular/bronchiectatic (NB), fibrocavitary (FC), NB + FC, and unclassified [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…obstruktive Lungenerkrankungen COPD/Emphysem [7, 14 -16] zystische Fibrose [17] schweres Asthma [18] Infektionen Pneumocystis-jirovecii-Pneumonie [19,20] Tuberkulose [7,21] nicht tuberkulöse Mykobakteriose [22] abszedierende Pneumonie…”
Section: Iatrogener Pneumothoraxunclassified
“…Treatment status was classified as never treated, previously treated, or currently treated. MAC isolates were identified as previously described [ 20 ]. Sputum smear or culture data were defined based on results obtained between 6 months before and 6 months after registration.…”
Section: Methodsmentioning
confidence: 99%